Análise de convergência de performance das bolsas de valores: a situação IBOVESPA no cenário mundial - Landim, Maria de Nazareth Pinheiro (2010)
This work analyses the validity of the hypothesis of common growth trend in the evolution of indices traded in the 36 of the major stock exchanges worldwide allocated in economies with different development levels, located on all continents, during the period from January 1998 to December 2007, based on semi parametric approach developed by Philips and Sul (2007). Since the index is a dynamic portfolio with specific properties of re-balancing, commonly used as a performance indicator of companies in a given country or specific economic sector, the empirical contributions can be related to the integration between financial markets and theory portfolio literature, allowing to evidence the existence of three convergence clubs, with very particular transition dynamics, whose composition seems has very specific characteristics. The first club has volatile indices with a reasonable level of maturity, situated in developing economies located mainly in Latin America and Central and with high inflation indices, being Ibovespa index the oldest in this group, while the second one is comprised of most indices, which are characterized by a higher level of maturity and tradition of financial markets and the development of economies, located mainly in Europe, North America and Asia. The third club has only four indices, with no clear standards in terms of macroeconomic, financial or geographical aspects.